PERANAN MAJELIS TAKLIM WAQIAH INDONESIA DALAM PEMBINAAN AKHLAK REMAJA DI PERUMAHAN JOYOGRAND MERJOSARI MALANG - Yulianto Eko Saputro; Rosichin Mansur; Fita Mustafida (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
This study aims to determine the role of the Indonesian waqiah majelis in adolescent moral development in the Merjosari Malang joyogrand housing complex. The problem found in Joyogrand's residential area, Merjosari sub-district, Malang, is still a lot of activities that can damage the morale of teenagers. Among them like hanging out accompanied by drinking (drunkenness), spending time playing games or gadgets together until the early hours of the morning, holding orchestras that often cause commotion and often come together with playing cards at night. This study uses descriptive qualitative methods and types of case studies. Where data collection is obtained from the results based on observation, interviews, and documentation. And analyzing data is done by data reduction, data presentation, and drawing conclusions. The results of this study are that the Indonesian majelis taklim waqiah is able to provide positive benefits to the congregation especially the teenagers.